2005
DOI: 10.1371/journal.pbio.0030101
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α Deficiency Causes Multi-System Energy Metabolic Derangements: Muscle Dysfunction, Abnormal Weight Control and Hepatic Steatosis

Abstract: The gene encoding the transcriptional coactivator peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) was targeted in mice. PGC-1α null (PGC-1α−/−) mice were viable. However, extensive phenotyping revealed multi-system abnormalities indicative of an abnormal energy metabolic phenotype. The postnatal growth of heart and slow-twitch skeletal muscle, organs with high mitochondrial energy demands, is blunted in PGC-1α−/− mice. With age, the PGC-1α−/− mice develop abnormally increased body fat, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

57
784
3
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 862 publications
(854 citation statements)
references
References 56 publications
(80 reference statements)
57
784
3
10
Order By: Relevance
“…PGC-1a also triggers mitochondrial biogenesis in skeletal and cardiac muscle 14,15 . Consistent with these findings, PGC-1a deficiency leads to multi-organ metabolic defects, including obesity, cold intolerance, hepatic steatosis, glucose imbalance and muscle dysfunction 16,17 .…”
supporting
confidence: 67%
“…PGC-1a also triggers mitochondrial biogenesis in skeletal and cardiac muscle 14,15 . Consistent with these findings, PGC-1a deficiency leads to multi-organ metabolic defects, including obesity, cold intolerance, hepatic steatosis, glucose imbalance and muscle dysfunction 16,17 .…”
supporting
confidence: 67%
“…They increase mitochondrial energy production by inducing the expression of genes that regulate fatty acid oxidation and by increasing mitochondrial activity (Kamei et al, 2003;Lin et al, 2003;Meirhaeghe et al, 2003;St-Pierre et al, 2003). Moreover, mice lacking either PGC-1a or PGC-1b exhibit little to no effect on mitochondrial mass and respiration activity (Lin et al, 2004;Leone et al, 2005;Lelliott et al, 2006;Sonoda et al, 2007). However, RNAimediated down-regulation of PGC-1b in PGC-1a À/À preadipocyte lines additively inhibits mitochondrial respiration (Uldry et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This elevation of G6pc and Pepck expression was potentially caused by elevated hepatic C/ebpβ (also known as Cebpb) gene expression [8]. In contrast, in their mice, Leone et al [9] observed euglycaemia in the fasted state with no elevation of G6pc, Pepck or C/ebpβ expression in the fed state and the same induction following fasting as seen in wild-type mice. The reasons for these differences are unclear.…”
Section: Introductionmentioning
confidence: 88%
“…The reasons for these differences are unclear. Interestingly, although Leone et al [9] observed no change in G6pc and Pepck expression and euglycaemia in the fasted state, HGP and gluconeogenic flux are altered in these mice as a consequence of altered tricarboxylic acid cycle flux [10]. In mice with a liver-specific deletion of the Pgc-1α gene, G6pc and Pepck expression were normal in the fed state but their induction by fasting was impaired [11].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation